FRI0156 Do changes in adipocytokines correlate with changes to disease activity in rheumatoid arthritis? findings from the tomorrow study. (15th June 2017) - Tada, M; Inui, K; Sugioka, Y; Okano, T; Mamoto, K; Koike, T; Nakamura, H
Abstract : Background: Cytokines released from mast cells evoke inflammation and correlate with arteriosclerotic lesions and autoimmune disease 1 . The relationship between disease activity and lipid metabolism is a notable in research surrounding rheumatoid arthritis (RA). RA patients without disease control reportedly show high titers of leptin or adiponectin as adipocytokines 2 . Objectives: We analyzed the interaction between changes in disease activity and adipocytokines using data from the TOMORROW (TO tal M anagement O f R isk factors in R heumatoid arthritis patients to lOW er morbidity and mortality clinical trial) study, a 10-year prospective study (registration number, UMIN000003876). Methods: We analyzed data collected from the cohort of the TOMORROW study including 193 patients with RA and age- and sex-matched 194 healthy individuals (controls). We compared changes in leptin and adiponectin (Δleptin and Δadiponectin) in both groups between baseline and after 3 years. Correlations with the change in disease activity (ΔDAS28ESR) during 3 years and changes in Δleptin and Δadiponectin in RA were investigated by univariate analysis. Results: Leptin levels increased in both groups. No significant differences in Δleptin were seen between RA (0.21 ng/ml) and controls (0.18 ng/ml; p=0.37). On the other hand, adiponectin was significantly decreased in controls (-3.3 μg/ml) compared to RA (-1.8 μg/ml; p=0.01). Negative correlations between Δleptin and Δadiponectin were detected in the RA group (r=-0.29, p<0.01). The correlation between adiponectin and DAS28ESR was positive both at baseline (r=0.22, p=0.01) and after 3 years (r=0.18, p=0.01). However, no such tendencies were seen for leptin. Table 1 shows details of the correlations with changes in adipocytokine. In terms of the relationship with ΔDAS28ESR, no correlation was seen with Δleptin (r=0.07, p=0.31) or Δadiponectin (r=-0.01, p=0.91). Changes in lipid metabolic markers and fat percentages were detected as predictive factors for Δadipocytokines. Conclusions: Leptin increased and adiponectin decreased over the course of 3 years. Correlations between Δadipocytokines and ΔDAS28ESR were not detected. RA patients with high disease activity show higher adiponectin titers. References: Benoist C., Mathis D. Mast cell in autoimmune disease. Nature. 2002; 420: 875–8. Cho H., Lin J., Chen W., et al. Baseline adiponectin and leptin levels in predicting an increased risk of disease activity in rheumatoid arthritis: a meta-analysis and systematic review. Autoimmunity. 2016; 49: 547–53. Disclosure of Interest: None declared